1997
DOI: 10.1162/jiec.1997.1.4.93
|View full text |Cite
|
Sign up to set email alerts
|

Combining SFA and LCA

Abstract: Summary This article describes a method that combines substance flow analysis (SFA) and life‐cycle assessment (LCA). It was used to provide a focus in the heated Swedish polyvinylchloride (PVC) debate. For Sweden's PVC chain, all emissions related to PVC were inventoried and translated into LCA‐theme scores. The theme scores were compared with total theme scores for all Swedish processes and were benchmarked on the basis of PVC's contribution to Sweden's gross national product (GNP). Mass flows oftwo PVC addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…These results agree with the findings from a comprehensive SFA of PVC in Sweden, performed by Tukker et al (1997). Their study showed that roof covering, plastisol building plate and automotive applications were by far the most important sources of phthalate outdoor emissions.…”
Section: Data Inventory and Calculation Of Substance Flowssupporting
confidence: 88%
See 1 more Smart Citation
“…These results agree with the findings from a comprehensive SFA of PVC in Sweden, performed by Tukker et al (1997). Their study showed that roof covering, plastisol building plate and automotive applications were by far the most important sources of phthalate outdoor emissions.…”
Section: Data Inventory and Calculation Of Substance Flowssupporting
confidence: 88%
“…SFAs can be valuable for predicting emissions to the environment, clarifying needs for action, and evaluating the efficiency of pollution control measures. Flow analyses have previously been performed for a number of materials, including PVC (Tukker et al 1997), and substances such as alkylphenols (Må nsson et al 2008) and phthalates (Hoffmann 1996). Most flow analyses cover the fluxes of goods and substances in a specific economic and geographic area, most often a country, a region or a city, leaving the results difficult to apply in other areas.…”
Section: Introductionmentioning
confidence: 99%
“…MFA is a systematic assessment of the flows and stocks of materials within a system defined in time and space (Brunner and Rechberger 2004). As such, MFA is the first step of every life cycle assessment (LCA) (Brunner and Rechberger 2004;Tukker et al 1997). The term material stands both for substances and goods.…”
Section: Sfa Applied To Precious Metals and Weee Recyclingmentioning
confidence: 99%
“…(c) Life cycle of a chemical in all of its product applications ( e.g. , analyzed through substance of material flow analyses either or not combined with RA 55 and/or LCA 56 ).…”
Section: Discussionmentioning
confidence: 99%